EFEKTIVITAS INFORMASI KOLEKSI KEBUN RAYA BOGOR MELALUI MEDIA KOMUNIKASI YANG TERINTEGRASI DENGAN WEB - Syafaat, Rifat (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This study was aimed to determine the effectiveness of the use of information media in the Bogor Botanical Gardens. The method used is a qualitative research method with a case study approach accompanied by interviews with random sampling techniques. The information media that became the research material was the information board in the Bogor Botanical Gardens. The Bogor Botanical Gardens are a plant conservation area under the supervision of the Indonesian Institute of Sciences. Although in its current development the function of the Bogor Botanical Gardens also includes a tourism function. To meet this need, the Bogor Botanical Gardens has prepared information media in the form of an information board that is integrated with the Bogor Botanical Garden's web page. From these developments the author intends to examine the effectiveness of the information media. As a result, there are still many things that must be addressed regarding the information media. Its presence is still considered ineffective for some people because of the difficulty of accessing web pages even though they are already using a QR code. Thus, this is an important note for the Bogor Botanical Gardens manager regarding the effectiveness of using the information media.